Risk factors for sports concussion: an evidence-based systematic review. Issue 2 (19th September 2013) - Abrahams, Shameemah; Fie, Sarah Mc; Patricios, Jon; Posthumus, Michael; September, Alison V
Abstract : Concussion is a common sports injury with approximately 1.6–3.8 million sport-related concussions reported in the USA annually. Identifying risk factors may help in preventing these injuries. This systematic review aims to identify such risk factors. Three electronic databases; ScienceDirect, PubMed and SpringerLink, were searched using the keywords 'RISK FACTORS' or 'PREDISPOSITION' in conjunction with 'SPORT' and 'CONCUSSION'. Based on the inclusion and exclusion criteria, 13 628 identified titles were independently analysed by two of the authors to a final list of 86 articles. Only articles with a level of evidence of I, II and III were included according to robust study design and data analysis. The level of certainty for each risk factor was determined. A high level of certainty for increased risk of a subsequent concussion in athletes sustaining more than one previous concussion was reported in 10 of 13 studies. Further, a high level of certainty was assigned to match play with all 29 studies reporting an increased concussion risk during matches. All other risk factors were evaluated as having a low level of certainty. Although several risk factors were identified from the appraised studies, prospective cohort studies, larger sample sizes, consistent and robust measures of risk should be employed in future research.